Meningkatkan Motivasi Belajar Peserta Didik melalui Pendekatan Culturally Responsive Teaching (CRT) pada Mata Pelajaran Pendidikan Pancasila Kelas V SDN 36 Cakranegara - Hidayati, Risma; Malik, Imam; Ayu Tirtawati, Sang (Mataram University, 2025)
This study aims to improve students’ learning motivation in the Pancasila Education subject by applying the Culturally Responsive Teaching (CRT) approach. The research was designed and conducted using the Classroom Action Research (CAR) method, implemented in two cycles. The subjects of this study were 24 fifth-grade students of SDN 36 Cakranegara in the 2024/2025 academic year. Data were collected through a student learning motivation questionnaire administered in each cycle. The questionnaire consisted of 23 items, including both positive and negative statements. The collected data were analyzed using quantitative techniques. The improvement in students’ learning motivation was reflected in the increase in the percentage of students categorized as having high motivation—from 16.67% in the pre-cycle to 33.33% in cycle I and 54.17% in cycle II. Meanwhile, the percentage of students with very high motivation increased from 8.33% in the pre-cycle to 16.67% in cycle I and 37.50% in cycle II. Based on these results, it can be concluded that the application of the Culturally Responsive Teaching (CRT) approach effectively enhances students’ learning motivation in Pancasila Education at SDN 36 Cakranegara.